Optimal Available Phosphorus Levels in Diets Containing Different Dicalcium Phosphate Particle Sizes for Japanese Quails - Nascimento, M. Q. [UNESP]; Vargas Junior, J. G.; Pinto, C. E. L.; Demuner, L. F.; Petrucci, F. B.; Vieites, F. M. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2019)
This experiment was conducted to investigate the effects available phosphorus levels and dicalcium phosphate particle size on the live performance, and egg parameters and bone parameters of Japanese quails in lay. The experimental diets were based on corn and soybean meal and formulated to contain 2900 kcal metabolizable energy (ME) kg(-1), 200 g kg(-1) crude protein (CP) and 30.5 g kg(-1) calcium (Ca). Feeds were supplied ad libitum. Laying Japanese quails (n=720, 20-wk-old) were distributed in a completely randomized design in a 5 x 2 factorial arrangement, with five levels of available phosphorus (avP; 1.0, 2.0, 3.0, 4.0, 5.0 g kg(-1)) and two dicalcium phosphate particle sizes (fine orcoarse), totaling ten treatments with eight replicates of nine birds each. Egg laying rate, feed intake per bird per day, egg weight, egg mass, feed conversion ratio per egg mass and per dozen eggs, eggshell, yolk and albumen relative and absolute weights, as well as bone ash, phosphorus, calcium, and magnesium contents were evaluated. Based on the results, avP recommendations for 20- to 32-wk-old laying Japanese quails varies according with phosphate source particle size and the dietary avP levels of 4.40 g kg(-1) and 3.85 g kg(-1)avP levels when using fine and coarse particle dicalcium phosphate, respectively, yielded the best results.
Keywords: Egg quality; macrominerals; mineral nutrition